LEPTIN AS AN INDUCER OF INFLAMMATION AND OXIDATIVE STRESS BY METABOLIC SYNDROME - I. D. Bespalovа (Бюллетень сибирской медицины)
Object of research: to explore the relationship of leptin level in blood serum with markers of systemic inflammation and spontaneous production of cytokines and reactive oxygen species by blood mononuclear leukocytes at metabolic syndrome.Material and methods. We conducted a study of 50 patients with essential hypertension stage II in conjunction with the metabolic syndrome. Along with a complete clinical, laboratory and instrumental examination adopted in specialized cardiological clinic, were determined the concentration of markers of systemic inflammation and leptin in blood serum, as well as the relative abundance of the surface markers CD4+-, CD8+-lymphocytes and CD36+-monocytes, the level of spontaneous production of proand antiinflammatory cytokines and active oxygen species by blood mononuclear leukocytes.Results. It was found that patients with essential hypertension stage II with the MS having hyperleptinemia statistically significantly differ both as greater activity of systemic inflammation, and have a greater percentage of CD4+-lymphocytes and a higher level of spontaneous production of blood mononuclear leukocytes a number of proinflammatory cytokines (IL-1β, IL-6, IL-8, TNF-α, MCP-1) and reactive oxygen species.